2021
DOI: 10.3389/fendo.2021.643851
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Is Involved in the Sexual Dimorphism of the Immune Response to Malaria

Abstract: Malaria is the leading cause of parasitic infection-related death globally. Additionally, malaria-associated mortality is higher in men than in women, and this sexual dimorphism reflects differences in innate and adaptive immune responses that are influenced by sex hormones. Normally, females develop more robust immune responses against parasites than males. However, most clinical and laboratory studies related to the immune response to malaria do not consider sex as a variable, and relatively few studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The interaction of oestrogens with their receptors activates different signalling pathways that modulate the expression of immune response genes [32]. We recently showed that parasitaemia of Plasmodium berghei ANKA-infected mice varies depending on 17βoestradiol concentration [20]. In this work, we found that tamoxifen, an estrogen receptor binding antagonist, increased parasitaemia.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The interaction of oestrogens with their receptors activates different signalling pathways that modulate the expression of immune response genes [32]. We recently showed that parasitaemia of Plasmodium berghei ANKA-infected mice varies depending on 17βoestradiol concentration [20]. In this work, we found that tamoxifen, an estrogen receptor binding antagonist, increased parasitaemia.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, 17β-oestradiol administration to intact female mice infected with P. berghei ANKA increases parasitaemia and decreases body weight. By contrast, reconstitution of gonadectomised female mice using 17β-oestradiol reduces parasitaemia and affects the immune response [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits a marked sexual dimorphism, with males showing higher parasitaemia, symptom severity and mortality than females. Sex hormones are involved in the sexual dimorphism of the immune response in malaria ( Lopes et al., 2016 ; Legorreta-Herrera et al., 2018 ; Cervantes-Candelas et al., 2021 ); oestrogens induce immunocompetence. In contrast, testosterone, the primary male hormone, generates immunosuppression ( Wichmann et al., 1996 ; Wunderlich et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…iPRs were initially described in the lymphocytes of pregnant women, while mPRs were described in T lymphocytes and are overexpressed during the luteal phase in CD8 + T lymphocytes. Differential expression of PRs may partially explain the differential activation of immune cells and differences in susceptibility to various infectious and noninfectious diseases between men and women [ 101 ].…”
Section: Sex Hormones and Periodontitismentioning
confidence: 99%